Analisis Pengaruh Produk Domestik Regional Bruto, Jumlah Penduduk, dan Upah Minimum Kabupaten/Kota Terhadap Tingkat Pengangguran di Malang Raya - Setyaningrum, Zakiyah Addini (Jurnal Ilmiah Mahasiswa FEB, 2016)
Unemployment is an image of the labor market's inability to absorb certain area of available labor force. The average unemployment rate in Malang is 5.27%. According to information from the Central Bureau of Statistics that the normal level of unemployment in the region is not more than 4%. From the existing phenomenon can be seen that there is an inequality between economic growth and the unemployment rate in Malang Raya. The objective of this research is to analyze the influence of regional gross domestic product, population, minimum wage rate of district / city on the unemployment rate in Malang within 2004-2013. Dependent variable of this study is unemployment, while the independent variables of this research are the GDP, number of population , and the minimum wage rate of districts / cities. The data used is the data panel in research area Malang Raya that includes Malang City, Malang Regency, and Batu City with a time series of 10 years (2004-2013). Source of data used comes from the literature, BPS, journals, and previous research. The data is processed using the Random Effect Model (REM) analysis with the software STATA 10. The results showed that the GDP variable (X1) has a significant positive effect on the unemployment rate (Y), number of population variable (X2) has significant negative effect on the unemployment rate (Y), and minimum wage rate of districts / cities variable (X3) has significant negative effect on the unemployment rate (Y). Keywords: GDP, Unemployment Rate, Number of Population, Minimum Wage Rate